Indicadores de sustentabilidade em indústrias de vestuário no APL de Maringá/Cianorte - PR - Barcelos, Silvia Mara Bortoloto Damasceno (2012)
Latino "Sustentare" means to sustain, maintain, support, maintain in good repair, maintain and resist, hence the term sustainable means capable of being maintained or supported. Sustainability is based on the Triple Bottom Line, also called the pillars or dimensions. In this context, the various areas, has gained high importance due to environmental, economic and social rights, becoming a tool to differentiate between the organizations through which they can develop strategies and actions in order to be more competitive and sustainable. The organizations have entered information important in their decision making by means of sustainability indicators. One of the tools used worldwide and is considered one of the most complete in terms of indicators is the GRI (Global Reporting Initiative), which presents in its guidelines, key indicators, and additional sectoral organizations that assist in reporting sustainability, in order to position themselves differently towards their stakeholders. Therefore, this study was to evaluate the viability of the GRI-G3 guidelines for sustainability report generation in MPMDs apparel industries in Maringá APL / Cianorte - PR. Thus, the theoretical concepts discussed were related to sustainability, sustainability reporting and APL (Local Productive Arrangement). The method used in the research was deductive, being applied as a methodological approach, qualitative, exploratory and descriptive survey. To collect data was used two questionnaires, the first being to identify the level of importance of indicators and the status of each indicator and the second in the companies surveyed to identify the materiality of the indicators, i.e. indicators which are relevant to render the report sustainability according to the perception of managers. Data were tabulated and processed through a spreadsheet, calculating the weighted average. The results showed differences between what managers perceive as important and what they indicate as being relevant in the report included, as well as the status of each indicator, verifying the absence especially of a greater number of envir onmental indicators. However, according to the guidelines of the GRI-G3 reporting organization to a beginner is necessary to identify materiality responding to a minimum of 10 indicators, including at least one of each of the following performance areas: environmental, social and economic. Thus, was can conclude that the guidelines of the GRI-G3 proved to be enablers of sustainability report in MPMDs apparel industries in APL Maringá / Cianorte - PR, which have been met the requirements of the application level C for organizations beginners.